Sedation practice in six acute hospitals – a snapshot survey. (19th November 2014) - South West Anaesthetic Research Matrix (SWARM); Rutherford, William; Sneyd, Robert; Weekes, Lauren; Thomas, Megan; Edwards, Sean; Pugsley, Rebecca; Marshall, Simon; Bickley, James; Clark, Thomas; Franklin, Danielle; Hughes, Alexandra; et al.
Summary The number of UK hospital patients receiving procedural sedation remains unknown. Our trainee research network recorded all procedural sedation given over a 48‐h period at six acute hospitals in the South West of England. Three hundred and sixty patients aged between 1 and 96 years old were sedated. Most sedation occurred in endoscopy units (56.4%), operating theatres (30.3%) and cardiology departments (7.2%). Sedation was administered in 82.8% of cases by consultants, and in only 5.6% of cases by nurses. The most frequent sedative combination was midazolam and fentanyl, with median (IQR [range]) doses of 2 (2–3 [1–10]) mg and 50 (50–100 [10–300]) μg used, respectively. We tested a methodology that could be used in a UK‐wide denominator survey to describe sedation practice across the NHS. A national audit collecting serious adverse outcomes of sedation (severe harm or death) could then identify hotspots of sedation risk (clinical areas, patient groups, procedures and sedation techniques) where consistent application of current and improved standards might reduce harm.